Aortic flow below and visceral circulation during aortic counterpulsation: Evaluation of an in vitro model. (January 2022) - de Jong, Monique MJ; Parise, Orlando; Matteucci, Francesco; Rutten, Marcel; Devos, Maxime; Romano, Mario; Micali, Linda Renata; Parise, Gianmarco; Maessen, Jos G; Gelsomino, Sandro
Introduction: This study aimed to test a computer-driven cardiovascular model for the evaluation of the visceral flow during intra-aortic balloon pump (IABP) assistance. Methods: The model includes a systemic and pulmonary circulation as well as a heart contraction model. The straight polyurethane tube aorta had a single visceral while four windkessel components mimicked resistance compliance of the brachiocephalic, renal and sub-mesenteric, pulmonary, and systemic circulation. Twelve flow probes were placed in the circuit to measure pressures and flows with the IABP on and off. Results: With the balloon off, the meantime to reach the steady state was 48 ± 16 s; with the balloon on, this figure was 178 ± 20 s. The stability of pressure and flow signals was obtained after 72 ± 11 min. The number of cycles of stability of the system was 93 [86–103]. Measurements were reliable either with samples of 10 or 20 beats. Bland Altman method demonstrated the reliability of measurements. Finally, all measurements were comparable to published in vivo data. Conclusion: The presented mock circulation was reliable and gave values with high accuracy both at baseline and during mechanical assistance. This system allows evaluation of the mesenteric flow during IABP, under different clinical/hemodynamic conditions. Nonetheless, its translational potential needs to be further evaluated